POTENTIAL REFORM OF SERBIAN NETWORK OF BILATERAL INVESTMENT TREATIES: AN OPPORTUNITY FOR A NEW BEGINNING - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
In past several years many states have started a reform of their bilateral investment treaties (BITs). The idea behind this effort is to terminate altogether or to replace the existing BITs, often perceived as unbalanced instruments, focused solely on the protection of investors and containing broad and open language, with new treaties. Serbia is, at the moment, not engaged in such process. The paper offers an overview of the BITs currently in force in Serbia. It also discusses different options for inevitable reform of Serbian BITs, bearing in mind legal, economic and political implications of three alternatives: denunciation (unilateral termination) of the existing BITs, termination by consent and their replacement with new treaties.
Keywords: Bilateral Investment Treaties (BITs), foreign investments, investment arbitration, European Union.